2012
DOI: 10.1073/pnas.1208557109
|View full text |Cite
|
Sign up to set email alerts
|

Antisilencing role of the RNA-directed DNA methylation pathway and a histone acetyltransferase in Arabidopsis

Abstract: REPRESSOR OF SILENCING 1 (ROS1) is a DNA demethylation enzyme that was previously identified during a genetic screen for the silencing of both RD29A-LUC and 35S-NPTII transgenes on a T-DNA construct. Here we performed a genetic screen to identify additional mutants in which the 35S-NPTII transgene is silenced. We identified several alleles of ros1 and of the following components of the RNA-directed DNA methylation (RdDM) pathway: NRPD1 (the largest subunit of polymerase IV), RDR2, NRPE1 (the largest subunit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
99
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 36 publications
7
99
0
1
Order By: Relevance
“…14,22,23,[55][56][57][58] This distribution pattern is also in agreement with an anticorrelation of H3K23ac with DNA methylation. 18,59 Surprisingly, we found that H4K16ac and H3K23ac are also enriched across the gene-body of many lowly expressed genes in rice (Fig. 5C and 5D).…”
Section: Discussionmentioning
confidence: 90%
“…14,22,23,[55][56][57][58] This distribution pattern is also in agreement with an anticorrelation of H3K23ac with DNA methylation. 18,59 Surprisingly, we found that H4K16ac and H3K23ac are also enriched across the gene-body of many lowly expressed genes in rice (Fig. 5C and 5D).…”
Section: Discussionmentioning
confidence: 90%
“…Although genome-wide analysis of the relationship between H3K9me1/2 and RdDM targets has not been reported, multiple RdDM target loci were shown to associate with H3K9me2 (31,32). Based on these observations we propose a model that DTF1 assists in recruiting Pol IV to genomic regions associated with H3K9me1/2, possibly through the interaction with CLSY1.…”
Section: Discussionmentioning
confidence: 94%
“…dms3-4 was identified during a genetic screen for mutants that silence Pro35S:NPTII in a transgenic Arabidopsis line carrying expressed ProRD29A:LUC and Pro35S:NPTII (C24 accession, which was used as the wild type in this study; Li et al, 2012). We performed a forward genetic screen using an ethyl methanesulfonate (EMS)-mutagenized dms3-4 population to isolate the mutants that release the silenced Pro35S:NPTII in dms3-4.…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
“…In a previous study, we performed a genetic screen for additional ROS genes by using a transgenic Arabidopsis line that carries a T-DNA insertion expressing both the ProRD29A:LUC (firefly luciferase reporter driven by the stress-responsive RD29A promoter) gene and the Pro35S:NPTII (neomycin phosphotransferase II driven by the CaMV 35S promoter) gene. Using this screen, we identified several genes in the RNA-directed DNA methylation (RdDM) pathway whose mutations silence Pro35S:NPTII because of the reduced expression of ROS1, indicating that the RdDM pathway positively modulates ROS1 expression (Huettel et al, 2006;Li et al, 2012). One of these mutants isolated from the screen was defective in meristem silencing 3 (dms3-4; Li et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation